The Role Of Islamic Business Ethics In The Relationship Between Adaptability And The Business Performance Of Syariah Financial Institutions - Agus Putranto; Muhammad Trihudiyatmanto (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study was to analyze how much influence adaptability has on business performance. The variables studied were independent variables consisting of adaptability variables and the dependent variable was business performance with Islamic business ethics as a moderating variable.Method - The research data were obtained from BMT Marhamah employees in Wonosobo Regency. Sampling from the population using the census sampling method. The data were collected using a survey method, namely the questionnaire was delivered and taken directly to the research object. Data analysis used the Structural Equation Modeling (SEM) test by checking the independent variables, moderating variables and dependent variables.Result - From the research that has been done, it is found that adaptability has an effect on business performance at BMT Marhamah Wonosobo. Islamic business ethics affect business performance at BMT Marhamah Wonosobo. adaptability has an effect on business performance at BMT Marhamah Wonosobo with Islamic business ethics as a moderating variable. This means that Islamic business ethics moderates the relationship between adaptability and business performance at BMT Marhamah Wonosobo.Implication - This study examines Micro Syariah Financial Institutions in Indonesia.Originality- There is a difference between theory and practice in Islamic Microfinance Institutions in Indonesia.